Palliative care outcomes in adult intensive care units: A scoping review of potential quality indicators - Sri Setiyarini; Christantie Effendy; Heru Suwardianto (Physical Therapy Journal of Indonesia, 2025)
Background: While critical care focuses on survival, it may unintentionally overlook aspects of comfort, dignity, and communication that are essential to quality end-of-life care. This scoping review aimed to identify existing outcome indicators, highlight gaps, and propose potential quality indicators for palliative care in ICU settings. Methods: Fifty-seven databases were searched for relevant publications published between January 2000 and December 31, 2024. The inclusion criteria were full-text, peer-reviewed journal articles in English, consisting of final versions of original or review studies conducted in adult ICUs. Case studies, perspectives, editorials, and reports were excluded. This study used the preferred reporting items for systematic reviews and meta-analyses extension for scoping reviews (PRISMA-ScR) approach. We reviewed the literature across multiple databases, including PubMed, ProQuest, EBSCOhost, Scopus, ScienceDirect, and BASE. We carried out the ScR according to the structure suggested by Arksey and O'Malley. Results: This review included 57 studies, with a total of 158 codes representing 122 unique codes, which were grouped into 29 sub-themes (categories of palliative care outcomes) within five main themes: communication and palliative care consultation, end-of-life care decisions, symptom management and comfort, psychosocial well-being of patients and families, and ethics and the role of clinicians in palliative care. Additionally, unique categories were identified to reflect each of these themes. Conclusion: Outcomes have been highlighted as unique and significant palliative care outcomes for adult patients in ICU critical care settings, potentially becoming candidate quality indicators. The candidate outcome indicators for palliative care in the ICU in the future will contribute to more measurable and standardized outcome assessments.